PWE-240 Incidental diagnosis of inflammatory bowel disease in a British bowel cancer screening cohort: a multi-centre study. (28th May 2012) - Butcher, R O; Mehta, S J; Ahmad, O F; Stein, J; Ignjatovic, A; Loo, L E; Abbasi, A M; George, R; Prudham, R; Vega, R; McCartney, S; Bloom, S L; et al.
Abstract : Introduction: The UK Bowel Cancer Screening Programme (BCSP) was launched in 2006 and rolled out in successive waves covering the entire population of England and Wales. It screens individuals aged 60–69 years with a Faecal Occult Blood test (FOBt) followed by a screening colonoscopy if FOBt positive. Our study aimed to quantify the incidental diagnosis of Inflammatory Bowel Disease (IBD) through BCSP and patient outcome in this cohort. Methods: We conducted a retrospective review of BCSP outcomes at our centres from launch in February 2007 until September 2011. Screening data included the number of patients invited, number screened (FOBt outcome "normal" or "abnormal") and number of colonoscopies performed. In those with newly diagnosed IBD at colonoscopy confirmed on histology, clinical data including demographics, disease characteristics, treatment and outcome were obtained from case note and electronic patient record review. Results: Of 378 424 patients invited, 172 244 were screened, representing an uptake of 45.52% and FOBt positivity of 2.71%. Colonoscopy was performed in 4195 patients (female 1761). Polyps were detected in 1870 (40.14%), cancer in 279 (5.99%) and 1216 (26.10%) had a normal examination. 83 patients had endoscopic appearance suggestive of IBD, confirmed at histology in 44. Seven patients were excluded as the diagnosis of colitis preceded the screening examination on case note review. Eleven of 37 incidental cases were female. Median age at diagnosis was 64. Twelve patients had Crohn's disease (CD), 22 ulcerative colitis (UC) and three had IBD-type unclassified (IBDU). 31 patients had follow-up data available with a mean follow-up period of 24.4 months. Fifteen patients (48.4%) were asymptomatic at diagnosis. Mean values for CRP were 11.8, Hb 13.8, Platelets 278.5, and Albumin 42.9. Treatment included steroids (8), 5-ASA (25), immunomodulators (azathioprine 5; methotrexate 1) and anti-TNF (infliximab 2; adalimumab 1). None required surgery. Those requiring immunomodulators and/or anti-TNF therapy (male 4; female 1) had asymptomatic extensive UC, symptomatic left sided UC, symptomatic left-sided IBDU, symptomatic Crohn's colitis and symptomatic stricturing terminal ileal CD at diagnosis. Conclusion: An incidental diagnosis of IBD is not uncommon and with the advent of bowel cancer screening this number is set to increase. These patients may present an important model for study of early disease with novel insights and evolving treatment paradigms. Competing interests: None declared.